Confocal Laser Scanning Microscopy for Analysis of Pseudomonas aeruginosa Biofilm Architecture and Matrix Localization - Reichhardt, Courtney; Parsek, Matthew R. (Frontiers in Microbiology, 2019)
Most microbes assemble as biofilms, which are multicellular aggregates encased within a biopolymer-rich matrix. The biofilm matrix promotes bacterial association with the aggregates and shields against harsh conditions including antibiotic treatment. Microscopy of biofilms permits examination of biofilm architecture as well as the identification and localization of important biofilm matrix components. This review highlights microscopic approaches for analysis of Pseudomonas aeruginosa biofilms to investigate bacterial biofilm assembly and matrix composition and localization. Initial investigations using confocal laser scanning microscopy of biofilms provided information about the importance of key matrix components in elaborating biofilm aggregate structures. Additionally, staining of matrix components using specific labels, such as fluorescently-labeled lectins to stain matrix exopolysaccharides, revealed discrete localization of matrix components within the aggregates. In some cases, it was found that interacting matrix components co-localize in the aggregates. The study of bacterial biofilms using confocal laser scanning microscopy is continuing to develop as both our understanding of biofilm bacterial physiology and microscopy techniques advance. We conclude the article by describing some outstanding questions and a brief discussion of how microscopy can be used to identify the functional aspects of biofilm matrix components.